Six-Week Retention Rate of Immediate Postplacental Intrauterine Devices at a University Teaching Hospital [3N]. (May 2016) - Colwill, Alyssa Covelli; Sonalkar, Sarita; Sammel, Mary D.; Schreiber, Courtney
Abstract : INTRODUCTION: Our objective was to determine the 6-week retention rate of IUDs placed within ten minutes of placental delivery at a university teaching hospital. METHODS: We conducted a retrospective cohort study via chart review examining the 6-week retention rate of the TCu380A IUD placed within ten minutes of placental delivery in vaginal (n=139) and cesarean (n=73) deliveries. For women who did not attend their postpartum visit, we performed a phone questionnaire in which patients reported expulsions and performed a string check. Delivery rates, overall and by mode of delivery, were estimated using Kaplan-Meier methods which assumed a woman was censored at her last follow-up visit, or at 1 week postpartum (Method 1) or 6 weeks postpartum (Method 2) if no follow-up information was available. RESULTS: Among the 212 women who received an IUD, 158 women had follow-up information (75%). Among those with follow-up, 130 (82.3%) retained their IUD at 6 weeks (95% CI 77.8–86.8%). Assuming that women lost to follow-up retained their IUD for only 1 week (Method 1), 6 week retention rate was 67.7% (95% CI 60.8–73.5%). Assuming that women lost to follow-up retained their IUD for 6 weeks (Method 2), 6 week retention rate of an IUD was 95% (95% CI 91.6–97.6%). CONCLUSION: Our results suggest a high retention rate of IUDs placed after placental delivery. Further studies are needed to evaluate the incidence of LARC uptake in women who have post-placental IUD expulsions or removals, and the incidence of rapid repeat pregnancy in women who have immediate post-placental IUDs inserted.